"I don't want to take chances.": A qualitative exploration of surgical decision making in young breast cancer survivors. Issue 6 (6th April 2018) - Rosenberg, Shoshana M.; Greaney, Mary L.; Patenaude, Andrea F.; Sepucha, Karen R.; Meyer, Meghan E.; Partridge, Ann H.
Abstract: Objective: Young women with unilateral breast cancer are increasingly choosing contralateral prophylactic mastectomy (CPM), despite its limited medical benefit for most women. The purpose of this study was to better understand this choice through a qualitative exploration of surgical decision‐making in young survivors, including how issues particular to younger women affected their decision and the post‐surgical experience. Methods: Women age ≤ 40 years with stage 0 to III breast cancer, 1 to 3 years from diagnosis who had undergone breast cancer surgery were recruited to participate. Four focus groups were conducted: 2 with women who had bilateral mastectomy and 2 with women who kept their contralateral breast. Focus groups were recorded and transcribed with identifiers removed. Emergent themes were identified by thematic content analysis using NVivo 11. Results: Of the 20 participants, median age at diagnosis was 37 years. Emergent themes were categorized into the following domains: (1) emotions/feelings surrounding surgery/decision about surgery; (2) factors affecting the decision; (3) communication and interaction with the healthcare team; (4) impact on post‐surgical life and recovery; and (5) support needs. Young women who chose CPM often were concerned about a future breast event, despite this low risk, suggesting some gain peace of mind by choosing CPM. Young survivors also had many physical and emotional concerns after surgery for which they did not always feel prepared. Conclusions: Informational resources and decision aids may enhance patient‐doctor communication and help young survivors better understand risk and manage expectations surrounding short and longer‐term physical and emotional effects after surgery.